Penerapan Konseling Kelompok Dengan Pendekatan REBT (Rational Emotive Behavior Therapy) Menggunakan Teknik Reinforcement Terhadap Motivasi Belajar Siswa - Pasaribu, Putri Dirgahayu; Arsini, Yenti; As Syifa, Salsabila (Madani: Jurnal Ilmiah Multidisiplin, 2024)
One important part of the learning process is motivation. Learning motivation is an encouragement that has a big influence on learning and learning outcomes. The level of strong and weak motivation to learn in students is indicated by persistence in facing assignments, independent learning, enthusiasm for learning, carrying out assignments, emotions towards the learning situation or atmosphere, confidence in a matter, and liking to search for and solve problems. This is based on the results of observations, interviews and questionnaires. Learning motivation scale as a pretest. Several introductory questions are also considered capable of fostering students' curiosity about related learning material, the aim of which is to make students more active, braver and able to learn better (Bahrudin, 2014). The REBT approach aims to change the client's irrational views and beliefs into rational ones, helping to change attitudes, ways of thinking and perceptions, therefore clients are expected to be able to develop and achieve optimal self-realization. The research method used is a literature review which is supported by data from several articles, source books and other supporting documents. The research results show that student motivation to learn is an important thing needed in the process of achieving optimal learning outcomes. One approach in guidance and counseling that can increase students' learning motivation is REBT which can help students open their horizons and have rational thinking in actions related to learning goals.